Permissible and prohibited animals in Islam: insights from the Qur’an and Hadis - Saidin, Nurulaina; Yaakob, Mohd Ashrof Zaki (Universiti Teknologi MARA (UiTM), Malaysia, 2025)
This article explores the Islamic dietary laws regarding halal and haram animals as derived from the Qur’an and authentic hadis. The fundamental principle in Islamic jurisprudence is that all good and wholesome (ṭayyib) things are permissible, while harmful and impure (khabīth) things are prohibited. Evidence from the Qur’an highlights the permissibility of most four-legged and aquatic animals, with certain restrictions, while the Hadith of the Prophet (PBUH) further clarifies specific rulings on animals such as locusts, horses, rabbits, and birds that do not prey on other creatures. Conversely, explicit prohibitions include pork, dead animals, flowing blood, and those slaughtered in the name of other than Allah, alongside animals with fangs, predatory birds, coprophagous animals, and creatures forbidden to be killed. This study also discusses the principle of necessity (ḍarūrah) which allows exceptions in dire circumstances. The findings affirm that Islamic dietary law is not only based on textual evidence but also emphasizes health, cleanliness, and the preservation of human life, reflecting Islam’s holistic approach to lawful consumption.